Interrelationships Among Sperm Quality Parameters, Cryocapacitation Status, Oxidative Markers and CASA Traits of Fresh and Frozen-thawed Semen of Gir and Murrah Bulls - Chaturvedi, Devangana; Dhami, Arjun J.; Chaudhari, Dinesh V. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
This investigation was carried out on three breeding bulls each of Gir and Murrah breeds to evaluate the interrelationships among sperm quality attributes, cryo-capacitation, oxidative markers and Biovis CASA traits of fresh and frozen thawed semen. The ejaculates (n=4/bull) having >75% initial motility were split-diluted @ 100 million sperm/mL in TFYG extender without (control) and with fortification of Mifepristone, Sericin and Taurine, filled in French mini straws, and were frozen using a programmable biofreezer. The straws were thawed in water bath at 37°C for 30 sec. The freshly diluted and frozen-thawed samples were assessed for various routine sperm quality parameters, cryo-capacitation status by CTC fluorescence, oxidative markers and for various motion characteristics/kinematics by Biovis CASA, the overall means of which are tabulated. The Pearson’s correlations studied among all these traits in freshly diluted and frozen thawed semen of both the species revealed that the sperm motility, HOS reactive sperm, live sperm and non-capacitated sperm were significantly (p<0.01) and positively interrelated (r= 0.29 to 0.88), while their correlations with capacitated & acrosome reacted sperm as well as seminal plasma GPx and MDA were negative (r= -0.25 to -0.99), but had no appreciable correlations with CASA traits of sperm, except initial motility with total and rapid progressive motile sperm, VCL, VAP and VSL of freshly diluted semen in Gir bulls (r= 0.28 to 0.41), and HOS reactive sperm with most of the CASA traits in Murrh bulls (r= 0.29 to 0.49). MDA activity of fresh semen and SOD of frozen-thawed semen in Murrah bulls also showed significant positive correlations with most of the CASA traits of respective stage. In post-thawed semen of both the species, all the sperm quality and capacitation traits including oxidative markers had significant positive or negative correlations with CASA derived total motile and rapid & slow progressive motile sperm (r= ± 0.29 to ± 0.70). Moreover, the sperm kinematics parameters of both fresh and frozen-thawed semen of both the species showed significant (p<0.01) positive interrelationship among themselves (r= 0.29 to 0.99), except slow progressive motile sperm and BCF in Gir bulls fresh semen and slow progressive motile sperm, ALH and DNC in Murrah bulls had negative correlations with other CASA traits, although no such specific trend was observed in post-thawed semen of either species. The first insemination conception rates also showed positive association with sperm motility, HOS reactive sperm, live sperm and non-capacitated sperm, SOD and GPx activity of plasma, but not with CASA traits. Thus, the initial and post-thawed sperm quality parameters including capacitation and oxidative status can predict the overall quality and fertility of bovine frozen-thawed semen.